Case Report: Nephrocalcinosis in an infant due to vitamin-D food supplement overdose - Pizzini, Carla; Ossato, Andrea; Realdon, Nicola; Tessari, Roberto (Frontiers in Pediatrics, 2024)
Background: Vitamin D is a vital lipophilic vitamin that plays a pivotal role in calcium regulation, bone metabolism, and overall health. It is of the utmost importance to maintain appropriate serum levels of vitamin D from the moment of birth. The recommended daily intake for infants under the age of 12 months is 400 IU. In Europe, vitamin D is available in two forms: as a medicinal product and as a food supplement. The food supplement market is experiencing rapid growth, yet it is characterised by a lack of harmonised regulations, which may give rise to potential risks associated with their widespread use. While food supplements are typically regarded as safe, there is a potential for adverse effects, particularly when dosages are not properly managed. Case report and management: This report presents the case of a 22-month-old girl who developed nephrocalcinosis as a result of an overdose of vitamin D from a dietary supplement purchased online. The initial presentation was characterised by symptoms such as polydipsia, polyuria and decreased growth. It was subsequently revealed that the child had been receiving an excessively high dose of vitamin D, amounting to 25 times the recommended amount, over a period of seven months. Despite normal calcium levels and renal function at the time of presentation, ultrasound imaging revealed the presence of earlystage nephrocalcinosis. The treatment plan involved hospital admission, intravenous hydration, a thiazide diuretic, potassium citrate, and a low-calcium diet. The vitamin D supplement was ceased. Over the course of a year, the patient demonstrated recovery in growth and normalization of vitamin D levels, although nephrocalcinosis remained stable.This case study highlights the potential dangers of unsupervised vitamin D supplementation, emphasising the importance of healthcare professionals exercising vigilance in prescribing and advising on vitamin D use, particularly in children. Furthermore, it underscores the necessity of establishing a database to track long-term outcomes in paediatric vitamin D intoxication cases, given the rarity of such incidents. This would facilitate the development of appropriate treatment protocols and provide valuable information to parents.